STUDI KORELASI PERILAKU PEKERJA TERHADAP PENERAPAN KESEHATAN DAN KESELAMATAN KERJA PADA PEMBANGUNAN POLIKLINIK FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA AMBON - Austin Caroles; Selly Metekohy; Henriette Dorothy Titaley (Journal Agregate, 2022)
Occupational Health and Safety is an effort to create a safe and healthy workplace so that it can increase work productivity. Occupational health is a condition where every worker must have a healthy state both physically, mentally and socially at work and must also maintain and protect health to work optimally and produce satisfactory work results. Based on the background of the problem, the author conducted a study to know how the relationship between the behavior of workers to the application of K3 in the Construction of the Polyclinic of the Faculty of Medicine, Pattimura University, Maluku, and whether the related Variables have a partial and simultaneous effect on the application of K3 or not. The methods carried out in this study there are 4 methods, namely: Validation Test, Reality Test, T-Test, and F Test. For the results of the Validation test, it is explained that all questions in the variables worker behavior and application of K3 are valid because the R count is greater than the R table and the Significance value does not exceed 0.05. For the results of the Reliability Test above, it is stated that the Question for Worker Behavior Variables, and Y is Reliable because the Cronbach Alpha value obtained exceeds 0.6. For the results of the T-test, it is known that the related variable has a partial effect on Variable Y. And from the results of the F test, it is known that the related variable has a simultaneous effect on Variable Y. The result of the study shows that there is a relationship between worker behavior and the application of K3, which is 95.1% and it is also known that the Worker Behavior Variable had a partial and simultaneous effect on the K3 Application Variable. Keywords: Correlation Study, Application of K3, Regression